2017
DOI: 10.1159/000471478
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes of the Carpentier-Edwards Perimount Pericardial Bioprosthesis in Chinese Patients with Single or Multiple Valve Replacement in Aortic, Mitral, or Tricuspid Positions

Abstract: Objectives: To report the safety and efficacy results of a 9- to 15-year follow-up investigation among patients who had received Carpentier-Edwards Perimount (CE-P) bovine pericardial bioprostheses (Edwards Lifesciences, Irvine, CA, USA) for valve replacement. Methods: This retrospective study investigated freedom from structural valve deterioration (SVD) as well as survival and reoperation among different age and etiology groups in patients who were implanted with a CE-P bioprosthesis at Guangdong General Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…It does however interfere with their true long-term survival analysis and durability of the CE-P valve. It is noteworthy that our survival is consistent with other studies; overall 5-, 10-and 15-year survival rate in China (81.58 66.19 and 57.33% [10]), overall 10-and 15-year survival rate in France (52.4 and 31.1% [9]), overall 5-, 10-and 15-year survival rate in a Canadian study (78, 55 and 34% [21]) and others [23]. We also investigated the survival from MACCE-cause mortality in order to more comprehensive describe the valve durability in combination with all causes of late death (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It does however interfere with their true long-term survival analysis and durability of the CE-P valve. It is noteworthy that our survival is consistent with other studies; overall 5-, 10-and 15-year survival rate in China (81.58 66.19 and 57.33% [10]), overall 10-and 15-year survival rate in France (52.4 and 31.1% [9]), overall 5-, 10-and 15-year survival rate in a Canadian study (78, 55 and 34% [21]) and others [23]. We also investigated the survival from MACCE-cause mortality in order to more comprehensive describe the valve durability in combination with all causes of late death (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…After patients surpass the general risk of the operation the first 30 days, the survival rate matches to the Danish population for 10 years. We may assume that the CE-P valves durability is being challenged by this point, which can also be supported by literature describing the development of SVD in CE-P at 9.24% after 10 years [ 10 ], and 18% after 15 years [ 7 ]. The Danish population is matched according to the mean age of our baseline (Median: 73 years, range: 20–91) which matches previous reports [ 3 , 7 9 , 19 , 21 , 22 ], and 12% of the cohort being < 65 years.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Even considering the level of healthcare service, the severity of patient condition at first visit, patient awareness of self-care, and economic conditions in China, survival analysis showed that the 10-year survival rate is satisfied compared to its foreign counterparts on average, especial in AVR and DVR (12)(13)(14)(15). The more comparable result is from Chinese local patients replaced with Perimount bovine pericardial bioprosthetic valves (14). In this study, the 5-year overall survival rate of AVR/MVR/DVR were 81.58%, 86.46% and 74.42% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparison with a similar Chinese cohort (n=225; mean age 61.2 years), treated with the Carpentier-Edwards Perimount (CE-P) bovine pericardial prosthesis, shows very similar results after 5 years (6). But after 10 years, the survival rates seem to favor the BalMedic bioprosthesis for aortic (80.6% vs. 66.2%) and double valve (82.9% vs. 55.9%) replacement.…”
mentioning
confidence: 90%